Restrukturisasi Manajemen Organisasi Sektor Publik dan Reformasi Birokrasi: Management Restructuring of Public Sector Organizations and Bureaucratic Reform - Faridawati Faridawati (AMANAH: Jurnal Manajemen Keuangan Sektor Publik, 2025)
Restructuring public sector organizational management is an effort to improve efficiency, effectiveness, and accountability in governance. This study aims to analyze and understand the concept, theory, and implementation of public sector organizational management restructuring. The research methods used are literature study and case analysis. The results show that restructuring public sector organizational management can improve efficiency and effectiveness, accountability and transparency, as well as the quality of public services and community participation. However, restructuring can also pose challenges and obstacles, such as lack of resources and employee resistance. Therefore, proper planning and implementation of restructuring, as well as effective monitoring and evaluation, are important to achieve restructuring objectives.